Analiza wytrzymałości ekonomicznej przedsiębiorstwa na potrzeby finansowania i współfinansowania projektów inwestycyjnych - Olkowska, Wiesława (Analysis of the Economic Strength of an Enterprise for the Purpose of Investment Projects Financing and Co-inancing, 2006)
The financial procedures concerning the investment capacity of enterprises presented in this paper enable to specify the mechanisms verifying the economic reality of particular investment decisions. Coherent systems for measuring and determining the economic limits of investment burdens are also described. The index of maximum net profit load in the part retained by investment expenditures can te fixed as early as at the concept/design stage. This is a starting point for establishing a long-range investment policy in an enterprise. In addition, the study focuses on financial factors as supporting tools, indicating external and internal sources of investment financing. It also points out to the possibility to acquire financial resources from the European Union, upon satisfying a set of specific investment support criteria. The calculation procedure described in the paper is simple and easy to employ, but its practical application must be preceded by creating a data bank and developing a computer programme.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 448-455